A 1984-Pixels, 1.26 nW/Pixel Retinal Prosthesis Chip With Time-Domain In-Pixel Image Processing and Bipolar Stimulating Electrode Sharing - Choi, Dong Hwi; Jee, Dong Woo (IEEE Journal of Solid-State Circuits, 2023)
This article presents a 1984-pixel retinal prosthesis (RP) chip with time-domain in-pixel image processing. The proposed time-domain image processing (TDIP) algorithm efficiently generates the edge-extracted stimulation and significantly reduces the stimulus power consumption. For the area- and power-efficient time-domain processing, a leakage current-based pulsewidth comparator (PWC) and its control scheme are also proposed. The proposed RP chip adopts the bipolar stimulation-based local return that minimizes image dispersion and a sequence control scheme that produces 1984 stimulation points with 1024 electrodes. The RP chip was implemented in a 180 nm CMOS process and achieved a power consumption of 1.26 nW/pixel, which is × 44.7 better than the previous state-of-the-art image processing RP chip.
Keywords: Bipolar stimulation; CMOS sensors; Delay; Edge extraction; Electrode time-sharing; Image edge detection; Images processing; Implantable chip; In-pixel processing; Local return; Low Power; Pixel processing; Power demands; Retina; Retinal prosthesis; Time domain images; Time-domain image processing; Time-sharing; Bipolar stimulation; CMOS sensor; edge-extraction; electrode time-sharing; implantable chip; in-pixel processing; local return; low power; retinal prosthesis (RP); time-domain image processing